PENGEMBANGAN SOAL EVALUASI HOTS DENGAN ADOBE ANIMATE CC2018 DALAM MATA PELAJARAN AL QUR’AN HADITS - Habibullah, Muhammad Romadlon; Nihayah, Hamidatun (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Learning evaluation is a process for determining the degree of achievement of learning objectives ya.ng have been studied before in a systematic way. The achievement of students in understanding the material that has been delivered by the teacher is also influenced by learning evaluation. Instead, teachers must be totality in understanding students with all their competencies and creativity. The media used in learning and evaluation is still relatively making it difficult for students to focus on learning. Included here is the subject of Quran Hadith. If you pay attention, students there will be able to concentrate on the learning process if the teacher is able to take advantage of interactive learning media. It was proven when PPL students there delivered material and questions using the Microsoft power point application. Learning activities in the class are getting more interesting. In the pre-digital era, the use of a.lat props can be a solution for learning media that is quite interesting. But now the all-digital one is able to be even more interesting. Departing from. This is why researchers took the initiative to develop teaching materials as learning resources by utilizing the Adobe Animate CC 2018 application. So from here, it is necessary to conduct research on the development of HOTS (Higher order Thinking Skill) evaluation questions with adobe animate cc2018 in learning Qur'an hadith for Madrasah Ibtidaiyyah. In this study, we will emphasize which Hots Evaluation Question Maker with Adobe animate CC2018 on the subject of the Qur'an Hadith for Madrasah Ibtidaiyyah and how the feasibility of the Hots Evaluation Question with Adobe animate CC2018 subject of the Qur'an Hadith in Madrasah Ibtidaiyyah. This research uses research and development method. development (research and developmennt). is a research method used to produce the product.